TO NUDGE OR NOT TO NUDGE HOUSEHOLDS: ENERGY EFFICIENCY CASE iN INDONESIA - Sudarmaji, Eka; Thalib, Supriadi (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the experiential electricity conservation through “Nudges”. “Nudges” are being widely used to encourage energy conservation. We used “nudge” to provide feedback to households on their own and their peers’ home electricity usage, the alternative way to make households save energy is by informing them that “comparable others” save more. We explored the idea that households can further improve this nudge by manipulating who the “comparable others” are. We also included twothree types of ‘nudge’ conditions: one where no feedback iswas provided, and one where only statistical feedback iswas provided (feedback about an average household). Research studiesy on “Nudges” framings that areis not only acceptable on specific manufacturing industry but also universally, given that the number of the industrial sectors was plentiful. There’s a huge opportunity to explore ‘Nudge’ framings especially in ‘energy efficiency’ in Indonesia, giving so many researchers focus on studying on ‘innovation’ and ’sustainability business’. The research’s model used the ‘Non-Equivalent Groups Design’ (NEGD) framework for both ‘the oberserved group’ and ‘control group’. The results of this study showed that ’social norm and curtailment (nudge type 1 & 2)’ have impacted on the motivation of reduction of electricity consumption in the rural area. The descriptive statistic and MANOVA Analysis were used to analyze the energy efficiency in a rural household in Indonesia.